Comparison between essential oil compositions of Zanthoxylum armatum DC. fruits grown at different altitudes and populations in Nepal. Issue 1 (1st January 2020) - Phuyal, Nirmala; Jha, Pramod Kumar; Raturi, Pankaj Prasad; Rajbhandary, Sangeeta
ABSTRACT: The fruits of Zanthoxylum armatum DC. were collected from different altitudes (1000–2000 m) and populations (wild and cultivated) from Salyan district, Nepal. The essential oil was extracted by Clevenger apparatus and the components were analyzed through GC-MS. The yield of essential oil obtained from hydro-distillation of fruits ranged from 2.72 to 7.6%. The maximum yield was 7.6% from wild fruits at 1600–1800 m altitude and the minimum was 2.72% from cultivated fruits at 1000–1200 m altitude. This was the highest recorded essential oil yield from Z. armatum fruits. A total of 13 volatile compounds were identified from the essential oil by GC-MS analysis. The major components were linalool, cinnamate (E)methyl, limonene, myrcene, sabinene and terpinen-4-ol, which were present in higher proportion in all the samples. Other components were identified in a very low proportion. The main component linalool occurred in the highest proportion (74.12%) from wild populations at 1600–1800 m altitude and the lowest (44.73%) was from cultivated populations at 1000–1200 m altitude. The highest proportion of linalool was also reported for the first time in this study from Z. armatum fruits. Among the six major components of the essential oil, terpinen-4-ol was present in the lowest proportion. Results of the present study indicated that the altitude and habitat types could affect the essential oil composition in Zanthoxylum armatum fruits.